Social Support, Religiosity, and Health Literacy as Predictors of Resilience in Pregnant Women during COVID-19 Pandemic - Nora Devi Irianjani; Elli Nur Hayati; Ma Teresa De Guzman (Journal of Educational, Health and Community Psychology, 2022)
Being pregnant during pandemic is challenging for women. A long and uncertain pandemic condition is accompanied by changes in health services, and other life conditions that require adaptation, coping, and resilient. This study aimed to examine the role of social support, religiosity, and health literacy as predictors of resilience among pregnant women during the COVID-19 pandemic in Yogyakarta, Indonesia. A purposive random sampling was employed to select participants of the survey, which was pregnant women that attended in antenatal care in Primary Health Care in Yogyakarta region. The scales of resilience, social support, religiosity, and health literacy was carried out to collect the data. Results showed that social support has a more significant contribution than health literacy and religiosity on resilience of pregnant women. Overall, there is a suitable health literacy mediation model between social support and resilience and religiosity with resilience. Social support, health literacy, and religiosity can be the predictors of resilience.